2009
DOI: 10.1016/j.autrev.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody targets and their cancer relationship in the pathogenicity of paraneoplastic retinopathy

Abstract: Paraneoplastic retinopathies (PR), including cancer-associated retinopathy (CAR) or the closely related melanoma-associated retinopathy (MAR) occur in a small subset of patients with retinal degeneration and systemic cancer. This autoimmune syndrome is characterized by sudden, progressive loss of vision in association with circulating anti-retinal autoantibodies. The PR syndromes are heterogeneous, may produce a number of ocular symptoms, and may be associated with several different neoplasms, including lung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 32 publications
2
173
1
3
Order By: Relevance
“…A related clinical phenotype was reported in patients with cutaneous malignant melanoma in 1988 [4], who were found to have autoantibodies to an unknown antigen on bipolar cells [5]. These paraneoplastic diseases were termed ‘cancer-associated retinopathy’ (CAR) and ‘melanoma-associated retinopathy’ (MAR), and since their discovery, hundreds of cases have been reported in the literature [6,7]. Subsequently, a non-paraneoplastic autoimmune retinopathy, of uncertain aetiology, similar in phenotype and electrophysiology to CAR, has also been reported [8].…”
Section: History and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A related clinical phenotype was reported in patients with cutaneous malignant melanoma in 1988 [4], who were found to have autoantibodies to an unknown antigen on bipolar cells [5]. These paraneoplastic diseases were termed ‘cancer-associated retinopathy’ (CAR) and ‘melanoma-associated retinopathy’ (MAR), and since their discovery, hundreds of cases have been reported in the literature [6,7]. Subsequently, a non-paraneoplastic autoimmune retinopathy, of uncertain aetiology, similar in phenotype and electrophysiology to CAR, has also been reported [8].…”
Section: History and Classificationmentioning
confidence: 99%
“…Predominant cone dysfunction is suggested by worsening acuity and colour vision, symptoms of photosensitivity, glare, flickering or shimmering lights and central scotoma, whilst impaired dark adaptation, night blindness, ring scotoma and peripheral field defects indicate predominant rod dysfunction [14,15]. Simultaneous rod and cone involvement is common, especially in association with antirecoverin antibodies, but the phenotype is heterogeneous [7,14]. Symptoms are typically worse than the clinical signs, and the fundus frequently appears normal [14].…”
Section: Clinical Phenotypesmentioning
confidence: 99%
“…Antirecoverin is an antibody associated with tumorassociated retinopathy. 13 Using the same immunohistochemical analytical methods performed by the same laboratory used in our study (Euroimmun, Lübeck, Germany), Dahm et al 6 also found a low prevalence of onconeural IgG autoantibodies in healthy individuals and in patients with schizophrenia, affective disorders, and personality disorders.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The mean age of onset has been described in the range of 55 to 65 years, with npAIR having a younger age of onset than CAR and MAR. [15][16][17] Cystoid macular edema has also been described in AIR. 14 Ancillary studies that can be useful in the diagnosis of AIR include visual field (VF) testing, electroretinography (ERG), fundus autofluorescence (FAF) imaging, and optical coherence tomography (OCT).…”
Section: Air: Clinical Featuresmentioning
confidence: 99%
“…[40][41][42] Autoantibodies targeting various other retinal proteins have also been implicated as putative causative agents based on the identification of these antibodies in the serum of patients with presumed AIR. These include antibodies against carbonic anhydrase II (which is abundant in ocular tissues) 17,43,44 and the retina-specific tubby-like protein 1 (TULP1). 45 The mere presence of autoantibodies in patient sera does not imply pathogenicity, as the antibodies could represent either "the secondary consequence of tissue damage, or the harmless footprint of an etiologic agent."…”
Section: Antiretinal Antibodies: Pathogenic Uncertaintiesmentioning
confidence: 99%